Correction: Examining the incidence of catastrophic health expenditures and its determinants using multilevel logistic regression in Malawi. - Atupele N Mulaga (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pone.0248752.].